Penguatan Hubungan Militer Australia dan Amerika Serikat dalam ANZUS Pada Tahun 2001 – 2005 - Istri Laksmi Dewi, Anak Agung (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2014), 2014)
ABSTRACT T he purpose of this research was to explain how Australia strengthening their military ties with United States after the Terrorist attacks in United States on 11 September 2001 that has destroyed the World Trade Center as one of the issues that change the pattern of the United States foreign relations, including the military ties between United States and Australia in the ANZUS.  ANZUS who had not previously been touted again by United States and Australia, since the events of 11 September has become increasingly active in strengthening the military ties between the two countries. Those can be seen from ANZUS active participation in any invasion that was made ??by the United States to the countries that are considered as the state sponsored of terrorism. Keywords: security alliance, foreign relations, terrorism, ANZUS